EXPLORING THE ROLE OF READING IN THE DEVELOPMENT OF WRITING ABILITIES - Solanki, Ankit; Patoliya, Virali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Reading is essential for the enhancement of writing skills, influencing vocabulary, grammar, syntax, and total language competence. The relationship between reading and writing is mutual, since exposure to various texts enhances writing abilities by fostering coherence, organization, and originality. This research examines the impact of reading on writing quality via the enhancement of comprehension, critical thinking, and stylistic expression. Various reading genres, such as fiction, nonfiction, and academic books, distinctively enhance writing development, promoting a more adaptive and diverse approach to written communication. Moreover, the research emphasizes the significance of both comprehensive and intense reading practices in enhancing writing fluency, clarity, and argumentation. The study investigates the impact of reading comprehension on writing structure and coherence, highlighting the significance of active reading strategies like annotation and summarizing. Moreover, motivation and reading habits substantially influence writing skill, underscoring the need for effective pedagogical ways to include reading into writing teaching. Notwithstanding the evident advantages, obstacles such as inadequate reading comprehension, restricted vocabulary, and insufficient access to excellent reading resources impede the complete actualization of the reading-writing link. Mitigating these obstacles via focused interventions and proactive reading techniques may improve writing efficacy. This research emphasizes that a robust reading habit cultivates clear, organized, and compelling writing, making reading an essential instrument for writing advancement.